A Systematic Review and Meta-analysis of the Prevalence of Community-Onset Bloodstream Infections among Hospitalized Patients in Africa and Asia - Marchello, Christian S. (Antimicrob Agents Chemother, 2019)
Community-onset bloodstream infections (CO-BSI) are major causes of severe febrile illness and death worldwide. In light of new data and the growing problem of antimicrobial resistance (AMR) among pathogens causing BSI, we undertook a systematic review of hospital-based studies of CO-BSI among patients hospitalized with fever. Without restriction to language or country, we searched PubMed, Web of Science, and Scopus for prospective hospital-based studies of culture-confirmed CO-BSI among febrile inpatients. We determined by study the prevalence of BSI among participants, the pathogens responsible for BSI, and the antimicrobial susceptibility patterns of pathogens causing BSI, according to place and time. Thirty-four (77.3%) of 44 eligible studies recruited 29,022 participants in Africa and Asia combined. Among participants in these two regions, the median prevalence of BSI was 12.5% (range, 2.0 to 48.4%); of 3,220 pathogens isolated, 1,119 (34.8%) were Salmonella enterica, 425 (13.2%) Streptococcus pneumoniae, and 282 (8.8%) Escherichia coli. Antimicrobial susceptibility testing was reported in 16 (36.4%) studies. When isolates collected prior to 2008 were compared to those collected in the period of 2008 through 2018, the proportions of typhoidal Salmonella and Staphylococcus aureus isolates resistant to several clinically relevant antimicrobials increased over time, while S. pneumoniae susceptibility was stable. CO-BSI remain a major cause of severe febrile illness among hospitalized patients in Africa and Asia, with S. enterica, S. pneumoniae, and E. coli predominating. There is a concerning increase in AMR among serious infections caused by community-onset pathogens. Ongoing surveillance is needed to inform empirical management and strategies to control AMR.